ICT organisations' minimal compliance with affirmative actions regulations: case of the Broad-Based Black Economic Empowerment (B-BBEE) ICT sector code in South Africa - Chimboza, Tendani Malunga (Department of Information Systems, 2023)
Research problem: Broad-Based Black Economic Empowerment (B-BBEE) is a legal framework established by the South African government to eradicate racial and gender exclusionary elements from the apartheid regime. This refers to the process called economic transformation. The B-BBEE Information Communication and Technology (ICT) Sector Code is the primary regulatory instrument for regulating ICT organisations' economic transformation activities. Organisational minimal compliance with the B-BBEE ICT Sector Code is the primary obstacle to including Black people in ICT business. Minimal compliance is a compliance behaviour that looks good on the letter of the law but does not transform the intended systems. While ICT organisations have good B-BBEE certificates, the points earned in the compliance process have not been translating into transformation. In 2020, 17 years after the introduction of the B-BBEE Act, the ICT Sector Council reported that ICT organisations had not made real progress in racial inclusivity in ownership and management structures. Minimal compliance with the B-BBEE ICT Sector Code reveals a policy enforcement dilemma where compliance with regulation makes no social change. Purpose of the research: The study interrogated how contextual factors affect minimal compliance with affirmative action regulations such as the B-BBEE ICT Sector Code. The study is a response to the call for Information Systems researchers to investigate the role of ICTs in achieving social justice and the socio-technical aspects that affect ICT enterprises. Investigating these kinds of regulations in Information Systems research also reveals how ICT business interacts with aspects of the socio-political context in post-colonial contexts such as South Africa. Methodology: This is a qualitative inquiry guided by a critical research paradigm. Data was collected through interviews, observations, and document analysis in various touchpoints of the B-BBEE ICT Sector Code. We employed thematic analysis and content analysis to analyse the research data. We developed a conceptual framework that suggests that minimal compliance stems from the need to protect the achievement of organisational goals. Key findings: Factors that affect minimal compliance with the B-BBEE ICT Sector Code are the organisational perception of the policy implementation context, organisational logic of action, and organisational legitimisation. ICT organisations leverage regulatory loopholes (e.g., pointsystem compliance) in the B-BBEE ICT Sector Code to comply with it in a manner that does not add value for the beneficiaries but allows them to achieve their organisational goals. ICT organisations responded to B-BBEE regulatory requirements through two utilitarian logics (goal prioritisation and maintaining status quo). Businesses are pragmatic institutions! This phrase surfaces every time a question B-BBEE compliance comes up. When they introduced the point-system compliance, B-BBEE policymakers did not consider the granular details concerning the complexity inherent in the South African historical context that would affect Black people's involvement in the digital economy. Quantifying the involvement of Black people in the ICT sector has resulted in the commoditisation of gender and race – making the beneficiaries the means to an end through B-BBEE points. The point-system compliance mechanism is the supreme loophole of the B- BBEE policy implementation context. The point-system enforcement mechanism propels ICT organisations to protect the achievement of their economic goals while neglecting the transformation agenda. Ideological discourses such as “B-BBEE compliance is anti-FDI, BBBEE compliance is costly, and B-BBEE compliance is complex” continue to thrive as legitimisation mechanisms to justify minimal compliance behaviour and its outcome. Research contribution: The study is rich with new knowledge about ICT organisational response to affirmative action policies in post-colonial contexts. The focus on the B-BBEE ICT Sector Code revealed policy discrepancies that future policymakers may consider ensuring that transformation takes place. International actors may benefit from the study's practical contribution to B-BBEE compliance processes, and the stakeholders involved. The study contributes to theory by proposing a conceptual framework for minimal compliance behaviour. The conceptual framework proposes three factors to be considered while analysing compliance behaviour: policy implementation context, organisational logics of action, and organisational legitimisation. Through this conceptual framework, the study shows that minimal compliance behaviour is mostly viewed as a binary behaviour – compliance or noncompliance. The compliance behaviour that looks good in the letter of the law but does not solve the problems that warrant policy introduction is taken for granted. The methodological contribution of the study rests in the use of multiple data sources that provided a heterogeneous perspective on B-BBEE compliance. Moreover, a critical interrogation of compliance behaviour is instrumental in illuminating mechanisms used by dominant powers to maintain hegemony by going around the regulations.